Simplify

6^log(36)9

Simplify

6^log(36)9

Tutors, please sign in to answer this question.

Wilton, CT

6^{(log369)}=6^{(log69/log636)}=6^{(log69)/2}=√9=3, since 6^{log69}=9

Katy, TX

6^(log_{36}9)

Use "change of base":

log_{36} 9 = (log_{6} 9)/(log_{6} 36)

Since log_{6} 36 = 2,

6^(log_{36}9) = 6^((log_{6} 9)/2) = (6^(log_{6} 9))^{1/2}

(6^(log_{6} 9))^{1/2}

Since 6^(log_{6} 9) = 9

(9)^{1/2} = sqrt(9) = 3

Answer:

3

Use "change of base":

log

Since log

6^(log

(6^(log

Since 6^(log

(9)

Answer:

3

John E.

Physics and Math tutor - Masters from Cornell and Columbia University

New York, NY

4.8
(124 ratings)

Gilant P.

Miss Gil: Cares & Gets Results - Regents, SAT & NYS ELA & Math Exams

Jamaica, NY

4.8
(1403 ratings)

Wesley L.

Premier MIT Math Tutor and SHSAT/SAT/ACT Specialist

New York, NY

5.0
(199 ratings)

- Math 6761
- Algebra 1 3037
- Algebra 2 2685
- Word Problem 3742
- Algebra Help 868
- Math Help 3982
- Algebra Word Problem 1908
- College Algebra 785
- Linear 111
- Algebra Equation 286

Find a tutor fast. Get the app.

Are you a tutor? Get the app for tutors

© 2005 - 2016 WyzAnt, Inc. - All Rights Reserved

## Comments